Une plaquette d’ivoire sculpté de l’Antiquité tardive dans la grande villa périurbaine de “Lazenay” à Bourges (Cher) - Jean-Claude Béal; Alain Ferdière (Revue Archéologique du Centre de la France)
During the excavation of a rich Late-Empire rubbish-area in 1975 on the large peri-urban villa of Bourges “Lazenay”, a decorative element (relief) carved in ivory was discovered. The examination of the associated furniture makes it possible to specify the date of burial and the status of the site at that time. The study of the object itself shows a remarkable element that undoubtedly contributes to a prestigious furniture decoration. The proposed comparisons confirm the exceptional character of this artefact, in a villa-palace, probably then of a high-ranking figure from the biturige society of late antiquity.